Revitalization of Ecotourism with Commercialization of Coral Transplantation Based on Productive Communities - Adhha, Nurul; Novriadi, Novriadi; Fahmi, Ahmad; Hutapea, Alfon; Azzahwa, Taufik; Khairurrijal Khairurrijal (Universitas Pendidikan Ganesha, 2024)
Destructive fishing practices and suboptimal tourism management threaten the sustainability of the underwater ecosystem and the welfare of the people of Pulau Pahawang Village. To overcome this problem, there needs to be an effort to revitalize ecotourism by commercializing productive community-based coral transplantation. This study aims to design and implement a community-based ecotourism revitalization program focusing on coral transplantation, waste management, and the development of sustainable ecotourism management. This type of research is community action research (PTM) with a participatory research design. The subjects of the study involved 50 members of the Pulau Pahawang Village community, consisting of 20 BumDes members and 30 Pokdarwis members. The data collection method used observation, interviews, and documentation. The instruments used were interview guides, observation sheets, and questionnaires. Data analysis was carried out using qualitative descriptive analysis techniques to describe the changes that occurred in the community and ecosystem. The results of the study showed that this program succeeded in issuing 15 Business Identification Numbers (NIB) for local business actors, developing Seawalker rides, and improving sustainable waste management. This program also succeeded in increasing public awareness of the importance of environmental conservation and good ecotourism management. This study concludes that a community-based approach to ecotourism revitalization can improve community welfare and maintain ecosystem sustainability.